Combined effect of cup abduction and anteversion angles on long-term wear evolution of PCD-on-PCD hip bearing couple. (2017) - Shankar, S.; Gowthaman, K.; Uddin, M.S.
This paper presents a three-dimensional (3D) finite element (FE) modelling for the estimation of wear evolution on the acetabulum cup against the femoral head for the combinations of different abduction angle (35°, 45° and 55°) and anteversion angle (0°, 10°, 20°, 30° and 40°) for PCD-on-PCD hip bearing components. By implementing the actual physiological hip gait loading conditions and the rotational movement of a normal walking cycle in the FE model, the contact pressure and the sliding distance were calculated to predict the wear. The cup surface was updated in a suitable interval of gait cycles for the estimation of wear. Wear was simulated for 20 years implant's life in a human body. Simulation results showed that higher abduction angle and lower anteversion angle result in the least linear and volumetric wear as compared to other conditions considered.